Minimal residual disease and outcomes of allogeneic hematopoietic stem cell transplantation in patients with acute leukemia - I. V. Galtseva; E. N. Parovichnikova; Yu. O. Davydova; N. M. Kapranov; K. A. Nikiforova; Yu. A. Chabaeva; L. A. Kuzmina; Z. V. Konova; I. S. Kastrikina; O. A. Aleshina; I. A. Lukianova; V. V. Troitskaya; et al. (Онкогематология)
Background. One approach to improving overall and relapsefree survival for patients with acute leukemia is allogeneic hematopoietic stem cell transplantation (allo-HSCT). The probability of relapse after allo-HSCT in acute leukemia patients may be influenced by many factors, including the presence of minimal residual disease (MR) before allo-HSCT. Aim. To evaluate the relationship between MR presence in first complete remission and probability of relapse after allo-HSCT in patients with acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL).Materials and methods. The study included 241 patients: 143 with AML and 98 with ALL (30 patients with Ph-positive leukemia, 22 patients with T-cell ALL and 46 patients with B-cell ALL) who received allo-HSCT at the National Medical Research Center for Hematology from September 2015 to July 2021. The MR analysis was performed using flow cytometry. Statistical analysis was performed using BIM SPSS v. 23 (SA).Results. Univariate event analysis revealed that in AML patients, poor prognosis was most associated with MRD-positive status before allo-HSCT (hazard ratio (HR) 10.249 (95 % confidence interval (CI) 4.137–25.388); p ˂ .0001). Multivariate analysis included MRD-positive status before allo-HSCT (HR 9.161 (95 % CI 3.513–23.652); p < 001), ELN risk (HR 4.423 (95 % CI 1.764–11.092); p ˂ 0.0034), and transplant source (bone marrow/peripheral stem cells) (HR 3.068 (95 % CI 1.188–7.924); p ˂ 0.0156). Three-year overall and relapse-free survival of AML patients in the first complete remission with MRD-positive status were statistically significantly worse than in patients with MRD-negative status (overall survival 43 % versus 78 %; p = 0.0004; relapse-free – 26 % versus 67 %; p ˂ .0001). In the univariate event analysis, it was found that MRD-positive status before allo-HSCT (HR 4.180 (95 % CI 1.333–13.112); p = 0.0142) was most associated with an unfavorable prognosis in ALL patients. In the multivariate analysis, only the MRD status before allo-HSCT was selected (p = 0.0005). The overall survival of MRD-positive ALL patients, although significantly worse, did not differ statistically significantly from that of MRD-negative patients who received allo-HSCT in the first complete remission (28 % versus 68 %; p = 0.09).Conclusion. MRD analysis before allo-HSCT helps to identify a group of patients with an extremely high risk of relapse after transplantation, which dictates the need to correct therapeutic tactics regarding the choice of donor, conditioning regimen, immunosuppressive therapy, or early prophylactic antirelapse therapy.